Impact of Mesoscale Circulation on the Structure of River Plumes During Large Rainfall Events Inshore of the East Australian Current - Li, Junde; Roughan, Moninya; Kerry, Colette; Rao, Shivanesh (Frontiers in Marine Science, 2022)
Estuarine outflow can have a significant impact on physical and ecological systems in the coastal ocean. Along southeastern Australia, inshore of the East Australian Current, the shelf is narrow, the coastal circulation is advection dominated, and river estuarine outflow tends to be low, hence river plumes have largely been ignored. For these reasons, we lack an understanding of the spatial and temporal evolution of river plumes during large rainfall events (which are projected to increase in frequency and intensity), and the interaction of the mesoscale circulation with the estuarine outflow remains to be explored. Using a high-resolution (750 m) hydrodynamic model, we simulate idealized plumes from 4 estuaries during three different mesoscale circulation scenarios and investigate the spatial and temporal evolution of the estuarine outflow under two contrasting rainfall events (normal and large). We explore the plume from the largest of the 4 rivers, the Hawkesbury River, to understand the impact of the mesoscale circulation. During the first EAC mode, the plume spreads both northward and southeastward. The offshore spread of the plume is the largest in this scenario (~12.5 km east of the river mouth) in the wet event. In the second EAC mode, this plume dispersal is toward the north and east, driven by the proximity of a cyclonic eddy on the shelf, with an eastward extension of 11 km. In the third EAC mode, most of this river plume spreads southward with some to the north, again dictated by the position of the cyclonic eddy. The cross-shelf dispersal is a minimum of 9.5 km from the river mouth. It takes around 6 days for the freshwater spatial extent of the plume in the wet event to return to the base case. These results show the importance of mesoscale EAC circulation on the shelf circulation when considering river plumes dispersal. Knowledge of the ultimate fate of riverborne material, dilution and cumulative effects will enable better environmental management of this dynamic region for the local government.